Multimethods study comparing the experiences of medical clinical academics with nurses, midwives and allied health professionals pursuing a clinical academic career. Issue 4 (1st April 2021) - Trusson, Diane; Rowley, Emma; Barratt, Jonathan
Abstract : Objectives: This study aimed to compare experiences of medical clinical academics (MCAs) with those of nurses, midwives and allied health professionals (NMAHPs) pursuing a clinical academic career. Design: A multimethods approach was used to elicit qualitative data. Both sets of participants completed similar online surveys followed by in-depth interviews to explore emerging themes. Setting: The research was conducted in the East Midlands of England, encompassing two Higher Education Institutions and four National Health Service Trusts. Participants: Surveys were completed by 67 NMAHPs and 73 MCA trainees. Sixteen participants from each group were interviewed following a similar interview schedule. Results: The survey data revealed notable differences in demographics of the two study populations, reflecting their different career structures. MCAs were younger and they all combined clinical and academic training, lengthening the time before qualification. In contrast, most NMAHPs had been in their clinical post for some years before embarking on a clinical academic pathway. Both routes had financial and personal repercussions and participants faced similar obstacles. However, there was also evidence of wide-ranging benefits from combining clinical and academic roles. Conclusions: Variations in experiences between the two study populations highlight a need for a clear academic pathway for all health professionals, as well as sufficient opportunities post-PhD to enable clinical academics to fully use their dual skills.